2007
DOI: 10.1007/s00198-007-0362-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nomogram for individualizing hip fracture risk in men and women

Abstract: The combination of BMD and non-invasive clinical risk factors in a nomogram could be useful for identifying high-risk individuals for intervention to reduce the risk of hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
189
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(196 citation statements)
references
References 32 publications
4
189
0
3
Order By: Relevance
“…An Australian study found that frailty-related risk factors such as advanced age, reduced weight, quadriceps weakness, and postural instability were each associated with increased risk of hip fracture. 10 Similarly, our findings have shown that frailty and frailty risk factors are associated with hip fracture risk. The same Australian study reported that combining FNBMD with clinical risk factors, which include age, prior fracture, and falls, provided a nomogram that predicted the risk of sustaining hip fracture over a median follow-up period of 13 years with an area under the ROC curve of 85%.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…An Australian study found that frailty-related risk factors such as advanced age, reduced weight, quadriceps weakness, and postural instability were each associated with increased risk of hip fracture. 10 Similarly, our findings have shown that frailty and frailty risk factors are associated with hip fracture risk. The same Australian study reported that combining FNBMD with clinical risk factors, which include age, prior fracture, and falls, provided a nomogram that predicted the risk of sustaining hip fracture over a median follow-up period of 13 years with an area under the ROC curve of 85%.…”
Section: Discussionsupporting
confidence: 74%
“…Other methods for predicting hip fractures, such as the Fracture Risk Assessment (FRAX), have used bone mineral density scores in combination with other selected risk factors, including several demographic characteristics and illnesses. 9,10 Although these methods are more inclusive than FNBMD alone, they still require bone mineral density testing and may require time for the physician to interview the patient and apply the tool. 10,11 There are inherent challenges with implementing ongoing screening programs designed to identify elderly patients with a high risk of hip fracture in the community.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the risk profile is largely based on clinical risk factors such as history of prior fracture, history of a fall, bone mineral density, body weight, and concomitant diseases. (6)(7)(8) Although these clinical risk factors are known to be associated with fracture risk, their ability to discriminate fracture from nonfracture cases is modest, with the AUC value ranging from 0.70 to 0.80. (7,8) Therefore, there is room for further improvement of fracture prognosis, and genetic profiling is potentially an important contributor to the enhancement of fracture risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Using established clinical risk factors, a number of prognostic models have been developed and implemented recently. (6)(7)(8) The predictive accuracy of these models has been less than perfect, with the area under the receiver operating characteristic curve (AUC) ranging between 0.70 and 0.80. (7,8) Most prognostic models have low sensitivity and high specificity.…”
Section: Introductionmentioning
confidence: 99%